Fibrous cellulose composite resin
By using a combination of urethane-esterified microfiber cellulose and urethane-esterified pulp, the problem of insufficient dispersion of microfibers in cellulose composite resin is solved, and the strength of the composite resin is significantly improved.
Patent Information
- Application Number
- CN202380048221.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-07
- Filing Date
- 2023-06-06
- Publication Date
- 2025-02-07
AI Technical Summary
Among the existing cellulose composite resins, the dispersion of the fine fibers is insufficient, which leads to insufficient strength of the composite resin, making it difficult to meet higher strength requirements.
The strength of the composite resin is increased by pre-carbamated pulp using a combination of urethane-based microfiber cellulose and urethane-based pulp.
The strength of the fibrous cellulose composite resin is significantly improved, the dispersion of microfiber cellulose is improved, and the overall performance of the composite resin is improved.
Smart Images

Figure BDA0005197081400000081 
Figure BDA0005197081400000261
Abstract
Description
Technical Field
[0001] The present invention relates to a fibrous cellulose composite resin. Background Art
[0002] In recent years, the use of microfibers such as cellulose nanofibers and microfiber cellulose (microfibrillated cellulose) as resin reinforcement materials has attracted attention. However, microfibers are hydrophilic, while resins are hydrophobic, so when microfibers are used as resin reinforcement materials, there are problems with the dispersibility of the microfibers. Therefore, the inventors have proposed a scheme of replacing the hydroxyl groups of microfibers with carbamate groups (see patent document 1). According to this scheme, the dispersibility of microfibers is improved, and thus the strength of composite resins is improved.
[0003] However, further improvement of strength is desired and various studies are being continued.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2020-163651 Summary of the invention
[0007] Problems to be solved by the invention
[0008] An object of the present invention is to provide a fibrous cellulose composite resin having improved strength.
[0009] Means for solving problems
[0010] In the above scheme (Patent Document 1), the inventors did not focus on the introduction of carbamate, but pursued the physical properties of fine fibers or other substances mixed in. In addition, it is also stated that pulp can be mixed with microfiber cellulose, but it is most preferred not to mix pulp, that is, the content is 0% by mass. This is because if pulp is mixed, the strength of the composite resin decreases. However, in the process of further repeated experiments, it was found that if pulp is pre-carbamateized, the strength of the composite resin is improved. Based on this discovery, the following means are conceivable.
[0011] That is, a fibrous cellulose composite resin characterized by:
[0012] Contains fibrous cellulose and resin,
[0013] As the above-mentioned fibrous cellulose,
[0014] Comprising carbamate-modified microfiber cellulose having an average fiber length of 0.15 mm to 0.90 mm and in which a part or all of the hydroxyl groups are substituted with carbamate groups, and carbamate-modified pulp having an average fiber length of 1.0 mm to 5.0 mm and in which a part or all of the hydroxyl groups are substituted with carbamate groups,
[0015] The fineness ratio of the urethanized microfiber cellulose is 70% or less.
[0016] Effects of the Invention
[0017] According to the present invention, a fibrous cellulose composite resin having improved strength is formed. DETAILED DESCRIPTION
[0018] Next, a specific embodiment will be described. It should be noted that this embodiment is an example of the present invention, and the scope of the present invention is not limited to the scope of this embodiment.
[0019] The fibrous cellulose composite resin of the present embodiment is characterized in that it comprises fibrous cellulose and a resin, wherein the fibrous cellulose comprises carbamate-modified microfiber cellulose having an average fiber length of 0.15 mm to 0.90 mm and a part or all of the hydroxyl groups being substituted with carbamate groups, and carbamate-modified pulp having an average fiber length of 1.0 mm to 5.0 mm and a part or all of the hydroxyl groups being substituted with carbamate groups, and the fineness of the carbamate-modified microfiber cellulose is 70% or less. This will be described in detail below.
[0020] (Microfiber cellulose)
[0021] In this embodiment, the fibrous cellulose is a microfiber cellulose (microfibrillated cellulose) having an average fiber diameter of 0.1 to 20 μm. If it is microfiber cellulose, the reinforcing effect of the resin is significantly improved. In addition, microfiber cellulose is easier to be modified (carbamate-modified) with a carbamate group than cellulose nanofibers, which are also microfibers. Among them, it is more preferred to carbamate-modify the cellulose raw material before microfiberization, in which case the microfiber cellulose and the cellulose nanofiber are equivalent.
[0022] Microfibril cellulose can be obtained by fibrillating (refining) a cellulose raw material (hereinafter also referred to as "raw pulp"). As the raw pulp, for example, one or more kinds of pulp can be selected from wood pulp made from broadleaf trees, coniferous trees, etc., non-wood pulp made from straw, bagasse, cotton, hemp, bast fiber, etc., and waste paper pulp (DIP) made from recycled waste paper, broken paper, etc. It should be noted that the above various raw materials can be in the form of a pulverized product (powdered product) such as a cellulose-based powder.
[0023] In order to avoid the mixing of impurities as much as possible, wood pulp is preferably used as the raw material pulp. As the wood pulp, for example, one or more kinds of chemical pulps such as broadleaf kraft pulp (LKP) and coniferous kraft pulp (NKP), mechanical pulp (TMP) and the like can be selected and used.
[0024] The hardwood kraft pulp may be hardwood bleached kraft pulp, hardwood unbleached kraft pulp, or hardwood semi-bleached kraft pulp. Similarly, the conifer kraft pulp may be conifer bleached kraft pulp, conifer unbleached kraft pulp, or conifer semi-bleached kraft pulp.
[0025] As the mechanical pulp, one or more kinds can be selected from stone ground pulp (SGP), pressure stone ground pulp (PGW), wood ground pulp (RGP), chemical fine grinding pulp (CGP), thermogrind pulp (TGP), grinding pulp (GP), thermomechanical pulp (TMP), chemical thermomechanical pulp (CTMP), refiner mechanical pulp (RMP), bleached thermomechanical pulp (BTMP) and the like.
[0026] The raw pulp can be pretreated by chemical methods before fiber opening. As pretreatment using chemical methods, for example, hydrolysis of polysaccharides using acid (acid treatment), hydrolysis of polysaccharides using enzymes (enzyme treatment), swelling of polysaccharides using alkali (alkali treatment), oxidation of polysaccharides using oxidants (oxidation treatment), reduction of polysaccharides using reducing agents (reduction treatment), etc. can be exemplified. Among them, as pretreatment using chemical methods, enzyme treatment is preferably performed, and more preferably, one or more treatments selected from acid treatment, alkali treatment, and oxidation treatment are also performed. The enzyme treatment is described in detail below.
[0027] As the enzyme used in the enzyme treatment, at least any one of a cellulase enzyme and a hemicellulase enzyme is preferably used, and the two are more preferably used in combination. When these enzymes are used, the fiber opening of the cellulose raw material becomes easier. It should be noted that the cellulase enzyme causes the decomposition of cellulose in the presence of water. In addition, the hemicellulase enzyme causes the decomposition of hemicellulose in the presence of water.
[0028] As cellulase enzymes, for example, enzymes produced by Trichoderma (filamentous fungi), Acremonium (filamentous fungi), Aspergillus (filamentous fungi), Phanerochaete (basidiomycete), Trametes (basidiomycete), Humicola (filamentous fungi), Bacillus (bacteria), Schizophyllum (basidiomycete), Streptomyces (bacteria), Pseudomonas (bacteria), etc. can be used. These cellulase enzymes can be purchased as reagents or commercial products. Examples of commercially available products include Cellulosin T2 (manufactured by HBI), Meicelase (manufactured by Meiji Seika Co., Ltd.), Novozyme 188 (manufactured by Novozyme), Multifect CX10L (manufactured by Genencor), and cellulase enzyme GC220 (manufactured by Genencor).
[0029] In addition, as a cellulase enzyme, any one of EG (endoglucanase) and CBH (cellobiohydrolase) can also be used. EG and CBH can be used alone or in combination. In addition, they can also be used in combination with a hemicellulase enzyme.
[0030] As the hemicellulase enzyme, for example, xylanase, which is an enzyme that decomposes xylan, mannase, which is an enzyme that decomposes mannan, arabanase, which is an enzyme that decomposes arabinan, etc. can be used. In addition, pectinase, which is an enzyme that decomposes pectin, can also be used.
[0031] Hemicellulose is a polysaccharide other than pectin that exists between cellulose microfibrils in plant cell walls. There are many types of hemicellulose, and they also differ depending on the type of wood and the wall layers of the cell wall. In the secondary wall of coniferous trees, glucomannan is the main component; in the secondary wall of broad-leaved trees, 4-O-methyl glucuronoxylan is the main component. Therefore, in the case of obtaining fine fibers from coniferous bleached kraft pulp (NBKP), it is preferred to use mannanase. In addition, in the case of obtaining fine fibers from broad-leaved bleached kraft pulp (LBKP), it is preferred to use xylanase.
[0032] The amount of enzyme added relative to the cellulose raw material is determined, for example, according to the type of enzyme, the type of raw wood (coniferous or broad-leaved tree), the type of mechanical pulp, etc. Among them, the amount of enzyme added relative to the cellulose raw material is preferably 0.1 to 3% by mass, more preferably 0.3 to 2.5% by mass, and particularly preferably 0.5 to 2% by mass. If the amount of enzyme added is less than 0.1% by mass, it is possible that the effect of the addition of the enzyme cannot be fully obtained. On the other hand, if the amount of enzyme added is higher than 3% by mass, cellulose is saccharified, and the yield of microfibril cellulose is likely to decrease. In addition, there is also a problem that the effect of the increase in the amount of addition cannot be confirmed to be improved.
[0033] When a cellulase enzyme is used as the enzyme, the pH during the enzyme treatment is preferably in the weakly acidic region (pH = 3.0 to 6.9) from the aspect of the reactivity of the enzyme reaction. On the other hand, when a hemicellulase enzyme is used as the enzyme, the pH during the enzyme treatment is preferably in the weakly alkaline region (pH = 7.1 to 10.0).
[0034] The temperature during the enzyme treatment is preferably 30 to 70° C., more preferably 35 to 65° C., and particularly preferably 40 to 60° C., when any of a cellulase enzyme and a hemicellulase enzyme is used as the enzyme. If the temperature during the enzyme treatment is 30° C. or higher, the enzyme activity is not easily reduced, and the treatment time can be prevented from being prolonged. On the other hand, when the temperature during the enzyme treatment is 70° C. or lower, the inactivation of the enzyme can be prevented.
[0035] The time of the enzyme treatment is determined by, for example, the type of enzyme, the temperature of the enzyme treatment, the pH during the enzyme treatment, etc. Among them, the general enzyme treatment time is 0.5 to 24 hours.
[0036] After the enzyme treatment, the enzyme is preferably inactivated. Examples of methods for inactivating the enzyme include a method of adding an alkaline aqueous solution (preferably pH 10 or higher, more preferably pH 11 or higher), and a method of adding hot water at 80 to 100°C.
[0037] Next, the method of the alkali treatment will be described.
[0038] When the pulp is subjected to an alkali treatment before fibrillation, the hydroxyl groups of the hemicellulose and cellulose contained in the pulp are partially dissociated and the molecules are anionized, thereby weakening the hydrogen bonds within and between the molecules, thereby promoting the dispersion of the cellulose raw material during fibrillation.
[0039] As the alkali used in the alkali treatment, for example, organic bases such as sodium hydroxide, lithium hydroxide, potassium hydroxide, aqueous ammonia solution, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, and benzyltrimethylammonium hydroxide can be used. Among them, sodium hydroxide is preferably used from the viewpoint of production cost.
[0040] When enzyme treatment, acid treatment or oxidation treatment is performed before fiber opening, the water retention of microfibril cellulose can be reduced, the crystallinity can be increased, and the homogeneity can be improved. In this regard, if the water retention of microfibril cellulose is low, it is easy to dehydrate, and the dehydration property of cellulose fiber slurry is improved.
[0041] When the raw material pulp is subjected to enzyme treatment, acid treatment, or oxidation treatment, the amorphous regions of hemicellulose or cellulose in the pulp are decomposed. As a result, the energy for fiber opening can be reduced, and the uniformity and dispersibility of the cellulose fibers can be improved. However, pretreatment reduces the aspect ratio of microfiber cellulose, so when using it as a reinforcing material (filler) for resin, it is preferable to avoid excessive pretreatment.
[0042] The fiber opening of the raw material pulp can be performed by beating the raw material pulp using a homogenizer such as a refiner, a high pressure homogenizer, a high pressure homogenizer, a grinder, a mortar friction machine such as a grinder, a mill, a single screw mixer, a multi-screw mixer, a kneading refiner, a jet mill, etc. Among them, it is preferably performed using a refiner or a jet mill.
[0043] In the present embodiment, microfiber cellulose refers to fibers whose average fiber width is thicker than that of cellulose nanofibers. Specifically, the average fiber diameter is, for example, 0.1 to 20 μm, preferably 1 to 19 μm, and more preferably 10 to 18 μm. If the average fiber diameter of the microfiber cellulose is lower than (less than) 0.1 μm, there is no change compared to the cellulose nanofiber, and the effect of improving the strength (especially the bending modulus) of the resin may not be fully obtained. In addition, the fiber opening time becomes longer and a large amount of energy is required. In addition, the dehydration of the cellulose fiber slurry deteriorates. If the dehydration deteriorates, a large amount of energy is required for drying. If a large amount of energy is applied during drying, the microfiber cellulose undergoes thermal degradation and the strength may be reduced. On the other hand, if the average fiber diameter of the microfiber cellulose is higher than (exceeds) 20 μm, there is no change compared to the pulp, and the reinforcement effect may become insufficient.
[0044] The method for measuring the average fiber diameter of microfiber cellulose (fine fibers) is as follows.
[0045] First, 100 ml of an aqueous dispersion of fine fibers having a solid content concentration of 0.01 to 0.1% by mass is filtered with a Teflon (registered trademark) membrane filter, and the solvent is replaced once with 100 ml of ethanol and three times with 20 ml of tert-butanol. Then, freeze-drying is performed, and osmium coating is performed to prepare a sample. For this sample, observation based on an electron microscope SEM image is performed at any magnification of 3,000 to 30,000 times depending on the width of the constituent fibers. Specifically, two diagonal lines are drawn on the observed image, and three straight lines passing through the intersection of the diagonal lines are drawn arbitrarily. The width of a total of 100 fibers intersecting with the three straight lines is then visually measured. In addition, the median diameter of the measured value is taken as the average fiber diameter.
[0046] The average fiber length of microfiber cellulose (average value of the length of single fibers) is preferably 0.15 to 0.90 mm, more preferably 0.20 to 0.70 mm, and particularly preferably 0.3 to 0.50 mm. If the average fiber length is less than 0.15 mm, a three-dimensional network of fibers cannot be formed, and the reinforcing effect (especially bending modulus) of the composite resin may be reduced. On the other hand, if the average fiber length is higher than 0.90 mm, the length is no different from that of the raw pulp, so the reinforcing effect may be insufficient.
[0047] The average fiber length of microfiber cellulose can be arbitrarily adjusted by, for example, selecting raw material pulp, pre-treating it, fibrillating it, and the like.
[0048] The average fiber length of the cellulose raw material used as the raw material of the microfiber cellulose is preferably 1.0 to 5.0 mm, more preferably 1.2 to 3.0 mm, and particularly preferably 1.5 to 2.5 mm. If the average fiber length of the cellulose raw material is less than 1.0 mm, the reinforcing effect of the resin during the fiber opening process may not be sufficiently obtained. On the other hand, if the average fiber length exceeds 5.0 mm, it may become disadvantageous in terms of the manufacturing cost during fiber opening.
[0049] The fiber length of the microfibril cellulose and the fibrillation rate described below were measured using a fiber analyzer "FS5" manufactured by Valmet.
[0050] The fineness of microfiber cellulose (Fine ratio; the proportion of fibers with a length of 0.2 mm or less) is preferably 35 to 70%, more preferably 36 to 55%, and particularly preferably 37 to 50%. If the fineness is less than 35%, the fiber size is too large and the bending properties may be insufficient. On the other hand, if the fineness exceeds 70%, the fiber size is too small and the fibers are strongly aggregated during drying. Even if urethanized pulp is present, the fibers may not be completely disintegrated by kneading shearing, and the dispersibility may become insufficient.
[0051] The aspect ratio of the microfiber cellulose is preferably 2 to 15,000, more preferably 10 to 10,000. If the aspect ratio is less than 2, a three-dimensional network cannot be constructed, so even if the average fiber length exceeds 0.15 mm, the reinforcing effect may be insufficient. On the other hand, if the aspect ratio is higher than 15,000, the microfiber cellulose becomes more entangled with each other, and the dispersion in the resin may be insufficient.
[0052] The aspect ratio is the value obtained by dividing the average fiber length by the average fiber width. It is known that the larger the aspect ratio, the more sites where hooks are generated, and thus the greater the reinforcing effect, but on the other hand, the ductility of the resin decreases in proportion to the increase in hooks.
[0053] The fibrillation rate of microfibril cellulose is preferably 1.0 to 30.0%, more preferably 1.5 to 20.0%, and particularly preferably 2.0 to 15.0%. If the fibrillation rate is higher than 30.0%, the contact area with water becomes too large, so even if the fiber can be opened within the range of an average fiber width of 0.1 μm or more, it may be difficult to dehydrate. On the other hand, if the fibrillation rate is lower than 1.0%, there are few hydrogen bonds between the fibrils, and a strong three-dimensional network may not be formed.
[0054] The crystallinity of microfiber cellulose is preferably 50% or more, more preferably 55% or more, and particularly preferably 60% or more. If the crystallinity is less than 50%, the strength of the fiber itself decreases, although the miscibility with pulp is improved, so there is a possibility that the strength of the resin cannot be improved. On the other hand, the crystallinity of microfiber cellulose is preferably 95% or less, more preferably 90% or less, and particularly preferably 85% or less. If the crystallinity is higher than 95%, the proportion of strong hydrogen bonds in the molecule increases, the fiber itself becomes rigid, and the dispersibility deteriorates.
[0055] The crystallinity of microfibril cellulose can be arbitrarily adjusted by, for example, selecting raw material pulp, pre-treating it, or refining it.
[0056] The crystallinity is a value measured in accordance with JIS K 0131 (1996).
[0057] The pulp viscosity of microfibril cellulose is preferably 2 cps or more, more preferably 4 cps or more. If the pulp viscosity of microfibril cellulose is less than 2 cps, it may be difficult to suppress aggregation of microfibril cellulose.
[0058] The pulp viscosity is a value measured in accordance with TAPPI T230.
[0059] The freeness of the microfibril cellulose is preferably 500 ml or less, more preferably 300 ml or less, and particularly preferably 100 ml or less. If the freeness of the microfibril cellulose is higher than 500 ml, the strength-enhancing effect of the resin may not be sufficiently obtained.
[0060] The freeness of microfiber cellulose is a value measured in accordance with JIS P8121-2 (2012).
[0061] The zeta potential of the microfibril cellulose is preferably -150 to 20 mV, more preferably -100 to 0 mV, and particularly preferably -80 to -10 mV. If the zeta potential is lower than -150 mV, the compatibility with the resin is significantly reduced, and the reinforcing effect may become insufficient. On the other hand, if the zeta potential is higher than 20 mV, the dispersion stability may be reduced.
[0062] The water retention of microfiber cellulose is preferably 80 to 400%, more preferably 90 to 350%, and particularly preferably 100 to 300%. If the water retention is less than 80%, there is no difference from the raw material pulp, so the reinforcing effect may be insufficient. On the other hand, if the water retention is higher than 400%, the dehydration property tends to be poor and aggregation is easily generated. In this regard, since the hydroxyl group of the fiber is substituted with a carbamate group, the water retention of microfiber cellulose can be further reduced, and the dehydration property and drying property can be improved.
[0063] The water retention of microfibril cellulose can be arbitrarily adjusted by, for example, selecting raw material pulp, pretreatment, fiber opening, and the like.
[0064] The water retention rate is a value measured in accordance with Japanese TAPPI No. 26 (2000).
[0065] The microfiber cellulose of this embodiment has a carbamate group. There is no particular limitation on how to make the microfiber cellulose have a carbamate group. For example, the carbamate group can be obtained by carbamate-esterifying a cellulose raw material, or by carbamate-esterifying a microfiber cellulose (a micronized cellulose raw material).
[0066] It should be noted that having a carbamate group refers to a state in which a carbamate group (ester of carbamic acid) is introduced into the fibrous cellulose. The carbamate group is a group represented by -O-CO-NH-, for example, a group represented by -O-CO-NH2, -O-CONHR, -O-CO-NR2, etc. That is, the carbamate group can be represented by the following structural formula (1).
[0067] [Chemistry 1]
[0068]
[0069] Here, n represents an integer greater than or equal to 1. Each R is independently at least any one of a saturated straight-chain hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated straight-chain hydrocarbon group, an unsaturated branched hydrocarbon group, an aromatic group, and a derivative thereof.
[0070] Examples of the saturated straight-chain hydrocarbon group include straight-chain alkyl groups having 1 to 10 carbon atoms, such as a methyl group, an ethyl group, and a propyl group.
[0071] Examples of the saturated branched hydrocarbon group include branched alkyl groups having 3 to 10 carbon atoms, such as isopropyl, sec-butyl, isobutyl, and tert-butyl.
[0072] Examples of the saturated cyclic hydrocarbon group include cycloalkyl groups such as cyclopentyl, cyclohexyl and norbornyl.
[0073] Examples of the unsaturated straight-chain hydrocarbon group include straight-chain alkenyl groups having 2 to 10 carbon atoms such as vinyl, propen-1-yl and propen-3-yl, and straight-chain alkynyl groups having 2 to 10 carbon atoms such as ethynyl, propyn-1-yl and propyn-3-yl.
[0074] Examples of the unsaturated branched hydrocarbon group include branched alkenyl groups having 3 to 10 carbon atoms such as propen-2-yl, buten-2-yl and buten-3-yl, and branched alkynyl groups having 4 to 10 carbon atoms such as butyn-3-yl.
[0075] Examples of the aromatic group include a phenyl group, a tolyl group, a xylyl group, and a naphthyl group.
[0076] Examples of derivative groups include groups in which one or more hydrogen atoms possessed by the above-mentioned saturated straight-chain hydrocarbon groups, saturated branched-chain hydrocarbon groups, saturated cyclic hydrocarbon groups, unsaturated straight-chain hydrocarbon groups, unsaturated branched-chain hydrocarbon groups and aromatic groups are replaced by substituents (e.g., hydroxyl groups, carboxyl groups, halogen atoms, etc.).
[0077] In the microfiber cellulose having a carbamate group (introduced with a carbamate group), a part or all of the hydroxyl groups with high polarity are replaced with carbamate groups with relatively low polarity. Therefore, the microfiber cellulose having a carbamate group has low hydrophilicity and high affinity with resins with low polarity. As a result, the microfiber cellulose having a carbamate group has excellent uniform dispersibility with the resin. In addition, the slurry of the microfiber cellulose having a carbamate group has low viscosity and good handling properties.
[0078] The substitution rate of the hydroxyl groups of the microfiber cellulose with carbamate groups is preferably 0.5 to 2 mmol / g, more preferably 0.6 to 1.8 mmol / g, and particularly preferably 0.7 to 1.6 mmol / g. If the substitution rate is less than 0.5 mmol / g, the microfiber cellulose will irreversibly aggregate due to hydrogen bonds from the hydroxyl groups during drying, and even if used in combination with pulp, it will not disperse during melt kneading, and the desired dispersibility may not be achieved. In addition, if the substitution rate is set to 0.5 mmol / g or more, the effect of introducing carbamate groups, especially the effect of improving the bending strength of the resin, can be reliably exerted. On the other hand, if the substitution rate exceeds 2 mmol / g, the cellulose fibers can no longer maintain the shape of the fibers, and even if used in combination with pulp, the reinforcing effect of the resin may not be fully obtained.
[0079] The substitution rate of carbamate groups (mmol / g) refers to the amount of carbamate groups contained per 1 g of the cellulose raw material having carbamate groups. Cellulose is a polymer having anhydroglucose as a structural unit, and each structural unit has three hydroxyl groups.
[0080] <Urethane Formulation>
[0081] Here, the method of carbamate-forming fibrous cellulose is described in detail.
[0082] Regarding the introduction of carbamate groups (carbamate treatment) into microfibril cellulose (cellulose raw material in the case of carbamate treatment before fibrillation; hereinafter also referred to as "microfibril cellulose, etc."), there are a method of carbamate treatment of the cellulose raw material and then micronizing it, and a method of carbamate treatment of the cellulose raw material and then micronizing it, as described above. In this regard, in this specification, the fibrillation of the cellulose raw material is first described, and then the carbamate treatment (modification) is described. However, either the fibrillation or the carbamate treatment may be performed first. Among them, it is preferred to perform the carbamate treatment first and then perform the fibrillation. This is because the dehydration efficiency of the cellulose raw material before fibrillation is high, and the cellulose raw material is in a state that is easy to fibrillate due to the heating accompanying the carbamate treatment.
[0083] The process of urethane-forming microfibril cellulose etc. can be mainly divided into, for example, a mixing process, a removal process and a heating process. It should be noted that the mixing process and the removal process may be collectively referred to as a preparation process for preparing a mixture to be subjected to a heating process.
[0084] In the mixing treatment, microfibril cellulose or the like (as described above, it may be a cellulose raw material; the same applies hereinafter) and urea or a urea derivative (hereinafter also referred to simply as "urea or the like") are mixed in a dispersion medium.
[0085] As urea or urea derivatives, for example, urea, thiourea, biuret, phenylurea, benzylurea, dimethylurea, diethylurea, tetramethylurea, compounds obtained by replacing the hydrogen atoms of urea with alkyl groups, etc. can be used. These ureas or urea derivatives can be used alone or in combination. Among them, urea is preferably used.
[0086] The lower limit of the mixing mass ratio of urea or the like to microfiber cellulose or the like (urea or the like / microfiber cellulose or the like) is preferably 10 / 100, more preferably 20 / 100. On the other hand, the upper limit is preferably 300 / 100, more preferably 200 / 100. By setting the mixing mass ratio to 10 / 100 or more, the efficiency of carbamate formation is improved. On the other hand, even if the mixing mass ratio is higher than 300 / 100, carbamate formation reaches a limit.
[0087] The dispersion medium is usually water, but other dispersion media such as alcohols and ethers, or mixtures of water and other dispersion media may also be used.
[0088] In the mixing treatment, for example, microfiber cellulose and the like and urea and the like may be added to water, microfiber cellulose and the like may be added to an aqueous solution of urea and the like, or urea and the like may be added to a slurry containing microfiber cellulose and the like. In addition, stirring may be performed after the addition for uniform mixing. In addition, other components may be included in the dispersion containing microfiber cellulose and the like and urea and the like.
[0089] In the removal treatment, the dispersion medium is removed from the dispersion liquid containing the microfibril cellulose and the like and urea and the like obtained in the mixing treatment. By removing the dispersion medium, urea and the like can be efficiently reacted in the subsequent heating treatment.
[0090] The dispersion medium is preferably removed by heating to volatilize the dispersion medium. According to this method, only the dispersion medium can be removed efficiently while components such as urea remain.
[0091] The lower limit of the heating temperature in the removal treatment is preferably 50° C., more preferably 70° C., and particularly preferably 90° C. when the dispersion medium is water. By setting the heating temperature to 50° C. or higher, the dispersion medium can be efficiently volatilized (removed). On the other hand, the upper limit of the heating temperature is preferably 120° C., more preferably 100° C. If the heating temperature is higher than 120° C., the dispersion medium reacts with urea, and urea may be decomposed alone.
[0092] The heating time in the removal treatment can be appropriately adjusted according to the solid content concentration of the dispersion, etc. Specifically, it is, for example, 6 to 24 hours.
[0093] In the heat treatment subsequent to the removal treatment, the mixture of microfibril cellulose and urea is subjected to heat treatment. In the heat treatment, part or all of the hydroxyl groups of the microfibril cellulose react with urea and the like and are replaced with carbamate groups. More specifically, when urea and the like are heated, they are decomposed into isocyanic acid and ammonia as shown in the following reaction formula (1). Moreover, the reactivity of isocyanic acid is very high, and for example, a carbamate group is formed at the hydroxyl group of cellulose as shown in the following reaction formula (2).
[0094] NH2-CO-NH2→HN=C=O+NH3…(1)
[0095] Cell-OH+HN=C=O→Cell-O-CO-NH2…(2)
[0096] The lower limit of the heating temperature in the heat treatment is preferably 120°C, more preferably 130°C, particularly preferably the melting point of urea (about 134°C) or higher, further preferably 140°C, and most preferably 150°C. By setting the heating temperature to 120°C or higher, urethane formation can be effectively performed. The upper limit of the heating temperature is preferably 200°C, more preferably 180°C, and particularly preferably 170°C. If the heating temperature is higher than 200°C, microfibril cellulose and the like are decomposed, and the reinforcing effect may become insufficient.
[0097] The lower limit of the heating time in the heat treatment is preferably 1 minute, more preferably 5 minutes, particularly preferably 30 minutes, further preferably 1 hour, and most preferably 2 hours. By setting the heating time to 1 minute or more, the urethanization reaction can be surely carried out. On the other hand, the upper limit of the heating time is preferably 15 hours, more preferably 10 hours. If the heating time is longer than 15 hours, it is not economical, and urethanization can be fully carried out with 15 hours.
[0098] However, the extension of the heating time will lead to the deterioration of the cellulose fibers. Therefore, the pH conditions in the heat treatment are very important. The pH is preferably an alkaline condition of pH 9 or above, more preferably pH 9 to 13, and particularly preferably pH 10 to 12. In addition, as a suboptimal strategy, it is an acidic condition or a neutral condition of pH 7 or below, preferably pH 3 to 7, and particularly preferably pH 4 to 7. If it is a neutral condition of pH 7 to 8, the average fiber length of the cellulose fibers becomes shorter, and the reinforcing effect of the resin may become worse. In contrast, if it is an alkaline condition of pH 9 or above, the reactivity of the cellulose fibers increases, the reaction to urea and the like is promoted, and the carbamate reaction can be carried out efficiently, so the average fiber length of the cellulose fibers can be fully ensured. On the other hand, if it is an acidic condition below pH 7, a reaction of decomposition into isocyanic acid and ammonia by urea and the like is carried out, the reaction to the cellulose fibers is promoted, and the carbamate reaction can be carried out efficiently, so the average fiber length of the cellulose fibers can be fully ensured. However, it is preferable to perform the heat treatment under alkaline conditions as much as possible. This is because if it is an acidic condition, acid hydrolysis of cellulose may be carried out.
[0099] The pH can be adjusted by adding an acidic compound (eg, acetic acid, citric acid, etc.) or a basic compound (eg, sodium hydroxide, calcium hydroxide, etc.) to the mixture.
[0100] As an apparatus for performing heating in the heat treatment, for example, a hot air dryer, a papermaking machine, a dry pulp machine, etc. can be used.
[0101] The mixture after the heating treatment may be dehydrated and washed. The dehydration and washing may be performed using water or the like. The unreacted and residual urea or the like can be removed by the dehydration and washing.
[0102] Microfibril cellulose is dispersed in an aqueous medium as needed to prepare a dispersion (slurry). The aqueous medium is particularly preferably entirely water, but an aqueous medium in which a portion is other liquids compatible with water may also be used. As other liquids, lower alcohols having a carbon number of 3 or less may be used.
[0103] The solid content concentration of the slurry is preferably 0.1 to 10.0% by mass, more preferably 0.5 to 5.0% by mass. If the solid content concentration is less than 0.1% by mass, excessive energy may be required during dehydration and drying. On the other hand, if the solid content concentration is higher than 10.0% by mass, the fluidity of the slurry itself decreases and uniform mixing may not be possible.
[0104] (pulp)
[0105] Next, the urethanized pulp will be described.
[0106] The fibrous cellulose composite resin of the present embodiment contains urethanized pulp. Pulp also has a function of greatly improving the dewaterability of the fibrous cellulose pulp.
[0107] The carbamate pulp can be obtained by carbamate-forming a raw material pulp. As the raw material pulp, the same raw material pulp as the raw material pulp of the carbamate-formed microfiber cellulose can be used, and it is preferable to use the same raw material pulp. If the same raw material pulp is used, the affinity of the cellulose fiber is improved, and as a result, the homogeneity of the cellulose fiber slurry is improved.
[0108] In addition, the method of carbamateizing the pulp may be the same as in the case of microfiber cellulose. Among them, the substitution rate (the substitution rate of carbamate groups to the hydroxyl groups of the pulp) is preferably 0.5 to 2 mmol / g, more preferably 0.6 to 1.8 mmol / g, and particularly preferably 0.7 to 1.6 mmol / g. If the substitution rate is less than 0.5 mmol / g, the pulps will irreversibly aggregate due to hydrogen bonds from the hydroxyl groups during drying, and will not disperse during melt kneading, and the desired dispersibility may not be achieved. On the other hand, if the substitution rate exceeds 2 mmol / g, the reinforcing properties of the pulp itself as a fiber will be lost, and therefore the desired mechanical properties may not be achieved.
[0109] The average fiber diameter of the urethanized pulp is preferably greater than 10 μm and less than 50 μm, more preferably 12 to 45 μm, and particularly preferably 14 to 40 μm. If the average fiber diameter is less than 10 μm, the area where the microfiber cellulose is adsorbed becomes smaller, so the microfiber cellulose itself agglomerates and may not be disintegrated by shearing during kneading. On the other hand, if the average fiber diameter is greater than (exceeds) 50 μm, the size of the fiber itself is large, so the fiber itself acts as a defect in the composite resin, and the desired mechanical properties may not be achieved.
[0110] The average fiber diameter of the urethanized pulp is a value measured in accordance with JIS P 8226.
[0111] The average fiber length (average value of the length of single fibers) of the urethanized pulp is preferably 1.0 to 5.0 mm, more preferably 1.2 to 4.5 mm, and particularly preferably 1.4 to 4.0 mm. If the average fiber length is less than 1.0 mm, the pulp itself will aggregate during drying and may not be disintegrated by shearing during kneading. On the other hand, if the average fiber length is more than 5.0 mm, the size of the fiber itself is large, so the fiber itself acts as a defect in the composite resin, and the desired mechanical properties may not be achieved.
[0112] The average fiber length of the urethanized pulp can be arbitrarily adjusted by, for example, selecting the raw material pulp.
[0113] The fiber length of the urethanized pulp was measured using a fiber analyzer "FS5" manufactured by Valmet.
[0114] The fineness of the urethanized pulp (the proportion of fibers with a fiber length of 0.2 mm or less) is preferably 1 to 20%, more preferably 2 to 17%, and particularly preferably 3 to 15%. If the fineness is higher than 15%, the pulp itself will aggregate during drying and may not be untied by shearing during kneading. On the other hand, if the fineness is lower than 1%, the pulp surface is too smooth and the microfibrils cannot be hooked and detached when attached, resulting in the microfibrils themselves agglomerating and not being untied by shearing during kneading.
[0115] The aspect ratio of the urethanized pulp is preferably 10 to 500, more preferably 15 to 400, and particularly preferably 20 to 300. If the aspect ratio is less than 10, the pulp fibers cannot exert the effect of fiber reinforcement and only exist in the composite resin, and even if microfibril cellulose is present, the pulp may become a defect in the composite resin and the mechanical properties may not be improved. On the other hand, if the aspect ratio is higher than 500, the fibers are entangled and agglomerated, and the effect of fiber reinforcement cannot be exerted. Even if microfibril cellulose is present, the pulp may become a defect in the composite resin and the mechanical properties may not be improved.
[0116] The aspect ratio is the value obtained by dividing the average fiber length by the average fiber width.
[0117] The crystallinity of the urethanized pulp is preferably 50% or more, more preferably 55% or more, and particularly preferably 60% or more. If the crystallinity is less than 50%, the strength of the pulp fiber as a fiber is insufficient, so even if microfibril cellulose is present, the pulp may become a defect in the composite resin and the mechanical properties may not be improved. On the other hand, the crystallinity of microfibril cellulose is preferably 95% or less, more preferably 90% or less, and particularly preferably 85% or less. If the crystallinity is higher than 95%, the pulp fiber becomes too rigid, the bending modulus is improved, but the softness as a composite resin is impaired, so even if microfibril cellulose is present, the bending strength and elongation may be reduced.
[0118] The crystallinity of microfibril cellulose can be arbitrarily adjusted by, for example, selecting the raw material pulp.
[0119] The crystallinity is a value measured in accordance with JIS K 0131 (1996).
[0120] The viscosity of the urethanized pulp is preferably 2 cps or more, more preferably 4 cps or more. If the viscosity is less than 2 cps, the polymerization degree is too low, so the strength of the fiber itself is insufficient, and even if microfibril cellulose is present, the pulp may become a defect in the composite resin and the mechanical properties may not be improved.
[0121] The pulp viscosity is a value measured in accordance with TAPPI T230.
[0122] (Relationship between microfiber cellulose and pulp)
[0123] First, the relationship between the urethanized microfiber cellulose and the urethanized pulp will be described.
[0124] The present inventors believed that, in view of the fact that microfibril cellulose aggregates during drying and the aggregates cannot be completely dissolved under external shear, if there is a scaffold in the system where microfibril cellulose aggregates, the microfibril cellulose is dried while adhering to the scaffold, and when sheared from the outside during kneading, the shear is efficiently transmitted to the microfibril cellulose through the scaffold, so that the microfibril cellulose can be dispersed. Based on this assumption, repeated and in-depth studies were conducted, and as a result, carbamate pulp was used as a scaffold. That is, the present inventors found that by using a mixed slurry of carbamate microfiber cellulose and carbamate pulp to prepare a composite resin, a fibrous cellulose composite resin with good fiber dispersibility in the resin and good bending properties can be obtained.
[0125] In such a background, the ratio of the amount (substitution rate) of the carbamate groups introduced into the carbamate microfiber cellulose and the carbamate pulp (substitution rate of carbamate pulp ÷ substitution rate of microfiber cellulose) is preferably 0.3 to 4.0, more preferably 0.4 to 3.0, and particularly preferably 0.5 to 2.0. If the ratio of the amount introduced is less than 0.3 or exceeds 4.0, the carbamate microfiber cellulose and the carbamate pulp have greatly different surface properties, and even if they are temporarily attached, they are easily separated, and the carbamate microfiber cellulose is aggregated with each other, and there is a possibility that it cannot be dispersed again during kneading.
[0126] The absolute value of the difference between the amount of carbamate groups introduced (substitution rate) of the carbamate microfiber cellulose and the carbamate pulp is preferably 0.01 to 2.00 mmol / g, more preferably 0.01 to 1.00 mmol / g, and particularly preferably 0.01 to 0.50 mmol / g. If it is out of the above range, the carbamate microfiber cellulose and the carbamate pulp do not interact with each other during drying, and the microfiber cellulose may aggregate with each other.
[0127] The ratio of the average fiber diameters of the urethanized microfiber cellulose and the urethanized pulp (average fiber width of the urethanized pulp÷average fiber width of the microfiber cellulose) is preferably 1.1 to 50.0, more preferably 1.1 to 30.0, and particularly preferably 1.1 to 10.0. If the ratio of the average fiber diameters is 1 or less, the urethanized pulp does not function as a support, and the microfiber cellulose aggregates with each other, which may make it impossible to redisperse during kneading. On the other hand, if the ratio of the average fiber diameters exceeds 50.0, the microfiber cellulose easily peels off even if it is temporarily attached due to the unevenness of the surface of the urethanized pulp, resulting in the microfiber cellulose aggregates with each other, which may make it impossible to redisperse during kneading.
[0128] The ratio of the average fiber length of the urethanized microfiber cellulose to the average fiber length of the urethanized pulp (average fiber length of the urethanized pulp÷average fiber length of the microfiber cellulose) is preferably 1.1 to 20.0, more preferably 1.5 to 15.0, and particularly preferably 2.0 to 10.0. If the ratio of the average fiber length is less than 1.1, the urethanized microfiber cellulose is firmly adsorbed to the urethanized pulp, and thus the microfiber cellulose may not be redispersed during kneading, resulting in no improvement in physical properties. On the other hand, if the ratio of the average fiber length exceeds 20.0, the microfiber cellulose is easily peeled off even if it is temporarily attached due to the unevenness of the surface of the urethanized pulp, resulting in the microfiber cellulose agglomerating with each other, and thus the microfiber cellulose may not be redispersed during kneading.
[0129] The dry mass ratio of the carbamate microfiber cellulose to the carbamate pulp (dry mass of carbamate pulp ÷ dry mass of microfiber cellulose) is preferably 0.01 to 100, more preferably 0.10 to 10, particularly preferably 0.30 to 3, and most preferably 0.30 to 1. If the blending ratio of the carbamate microfiber cellulose is relatively small, the cellulose fibers that contribute to the reinforcement of the resin are insufficient, and the reinforcement may become insufficient. On the other hand, if the blending ratio of the carbamate microfiber cellulose is relatively high, the fibers with large sizes that serve as a support, that is, the pulp, are insufficient, so that the microfiber cellulose aggregates with each other during drying, and the microfiber cellulose may not be opened by kneading shearing.
[0130] The pulp types of the carbamate-treated microfibril cellulose and the carbamate-treated pulp are preferably the same (broadleaf bleached kraft pulps, coniferous bleached kraft pulps, etc.). It is believed that by using the same pulp type, the type of hemicellulose is the same, so the microfibril cellulose and the pulp interact with each other during drying to facilitate adhesion, thereby preventing the microfibril cellulose from agglomerating with each other.
[0131] (Maleic anhydride modified resin)
[0132] The fibrous cellulose composite resin of this embodiment more preferably includes a maleic anhydride-modified resin, particularly maleic anhydride-modified polypropylene (MAPP). In this regard, MAPP is a polymer in which maleic anhydride reacts with PP and has a hydrophilic side chain from maleic anhydride (a side chain of a succinic anhydride structure in which the double bond of maleic anhydride disappears) on the hydrophobic PP main chain. In addition, the hydrophilic side chain of MAPP interacts (hydrogen bonds) with the carbamate group and hydroxyl group of the carbamate-modified cellulose fiber. Moreover, the hydrophilicity of the carbamate group is higher than that of the hydroxyl group, so it is easier to interact with the hydrophilic side chain of MAPP. In addition, MAPP has both hydrophilic and hydrophobic properties in the molecule, so it is difficult to arrange and difficult to crystallize. In addition, the carbamate group also helps to inhibit the coagulation of fibers. Due to the above reasons, MAPP and the carbamate-modified cellulose fibers that interact with the MAPP have very excellent dispersibility in the resin.
[0133] The blending amount of the maleic anhydride modified resin is preferably 1 to 200 parts by mass, more preferably 10 to 100 parts by mass, and particularly preferably 40 to 60 parts by mass relative to 100 parts by mass of the microfiber cellulose. If the blending amount of the maleic anhydride modified resin is less than 1 part by mass, the strength is not sufficiently improved. On the other hand, if the blending amount exceeds 200 parts by mass, it becomes excessive and there is a tendency for the strength to decrease.
[0134] The weight average molecular weight of the maleic anhydride modified resin is, for example, 1000 to 100000, preferably 3000 to 90000, and particularly preferably 5000 to 80000. If the weight average molecular weight is less than 1000, although it adheres to microfiber cellulose and pulp, it may be incompatible with the resin as the base material, and the homogeneity is poor. In addition, since the strength of maleic anhydride modified polypropylene itself is too low, although fiber reinforcement is performed, the overall physical properties may be insufficient. On the other hand, if the weight average molecular weight exceeds 100000, the viscosity becomes high during melting, resulting in parts that are not fully adhered to microfiber cellulose and pulp, and the fibers do not participate in the reinforcement of the entire resin, and the physical properties as a composite resin may be insufficient.
[0135] The acid value of the maleic anhydride modified resin is preferably 10 to 90 mgKOH / g, more preferably 20 to 80 mgKOH / g, and particularly preferably 30 to 70 mgKOH / g. If the acid value is less than 10 mgKOH / g, the adhesion to microfiber cellulose and pulp becomes insufficient, and the dispersibility may deteriorate. On the other hand, if the acid value exceeds 90 mgKOH / g, although the adhesion to microfiber cellulose and pulp is sufficient, the compatibility with the resin as the base material deteriorates, and the dispersibility in the composite resin may deteriorate.
[0136] (Polyethylene)
[0137] The fibrous cellulose composite resin of the present embodiment more preferably contains polyethylene, and more preferably contains polyethylene having a molecular weight of 1,000,000 g / mol or more.
[0138] The molecular weight of polyethylene is more preferably 1 million to 10 million g / mol, and particularly preferably 2 million to 800 g / mol. If the molecular weight is more than 1 million g / mol, the resins can interact with each other while interacting with the fibers during melting, and the composite resin can easily move as a whole in the mixer. It should be noted that PE with a molecular weight of more than 1 million g / mol is called UHMW-PE (ultra-high molecular weight polyethylene). On the other hand, if the molecular weight exceeds 10 million g / mol, the viscosity during melting becomes too low, so it is difficult to be compatible with the resin as the base material, and an uneven portion is produced, so that the strand may not be stably pulled out.
[0139] The melting point of polyethylene is preferably 125° C. or higher, more preferably 130 to 160° C., and particularly preferably 135 to 155° C. If the melting point is lower than 125° C., polyethylene may be immediately melted at the inlet of a kneading machine and adhere to the wall surface, and the polyethylene may be unevenly dispersed in the kneaded product. On the other hand, if the melting point exceeds 160° C., the kneading temperature must be excessively increased, and the microfiber cellulose may be colored due to thermal decomposition or the like.
[0140] The polyethylene may be in the form of powder, granules, flakes, blocks, etc. Among them, the polyethylene is preferably in the form of powder. When the polyethylene is in the form of powder, it is added to the aqueous dispersion of microfiber cellulose and pulp, mixed, and dried, and a part of it enters the gaps between the microfiber cellulose aggregates, thereby suppressing the aggregation to the extent that it can be redispersed by shearing of a kneader, compared with the case where no addition is made.
[0141] When the polyethylene is in powder form, the average particle size of the polyethylene is preferably 10 to 1000 μm, more preferably 15 to 100 μm, and particularly preferably 20 to 80 μm. If the average particle size is less than 10 μm, the polyethylene powders will aggregate and float in the aqueous dispersion of microfiber cellulose and pulp, and will not be able to enter the gaps between microfiber cellulose and pulp, and may not be able to fully exert the effect of suppressing aggregation. On the other hand, if the average particle size of the polypropylene powder is less than 100 μm, the polyethylene will easily enter between cellulose fibers when mixed with the slurry (MFC aqueous dispersion), and the polyethylene will be evenly distributed throughout the entire body when dried.
[0142] The average particle size is a value measured in accordance with ISO13320.
[0143] The maleic anhydride-modified polypropylene and the polyethylene are preferably contained in a ratio of preferably 10:90 to 90:10, more preferably 15:85 to 85:15, and particularly preferably 50:50 to 80:20 in terms of dry mass ratio. If the content ratio of the maleic anhydride-modified polypropylene is small, polyethylene enters during the adhesion of the microfiber cellulose and pulp to the maleic anhydride-modified polypropylene, which may hinder the adhesion of the maleic anhydride-modified polypropylene to the microfiber cellulose and pulp. On the other hand, if the content ratio of the maleic anhydride-modified polypropylene is large, although the adhesion of the maleic anhydride-modified polypropylene to the microfiber cellulose and pulp becomes good, the strength of the strand itself is insufficient during the strand processing during kneading and discharge, and the strand may not be pulled out.
[0144] (Non-interactive inorganic powder)
[0145] The fibrous cellulose composite resin of this embodiment preferably contains inorganic powder that does not interact with the fibrous cellulose. The inclusion of inorganic powder that does not interact is intended to physically inhibit hydrogen bonding between cellulose fibers.
[0146] Here, "no interaction" means no strong bonding with cellulose by covalent bonding, ionic bonding, or metallic bonding (that is, hydrogen bonding and bonding by van der Waals force are included in the concept of no interaction). Preferably, the strong bond is a bond having a bond energy exceeding 100 kJ / mol.
[0147] The inorganic powder that does not interact with each other is preferably an inorganic powder that has a small effect of dissociating the hydroxyl groups of the cellulose fibers into hydroxide ions when they coexist in the slurry. In this regard, if it is an inorganic powder, it is also advantageous in operation. Specifically, as a drying method for the composite resin, there are methods such as drying by making the aqueous dispersion directly contact a metal roller as a heat source (for example, drying using a Yankee dryer, a cylindrical dryer, etc.); a method of heating the aqueous dispersion without directly contacting the heat source, that is, a method of drying in the air (for example, drying using a constant temperature dryer, etc.). However, when the resin powder is dried in contact with a heated metal plate (for example, a Yankee dryer, a cylindrical dryer, etc.), a film is formed on the surface of the metal plate, the heat conduction becomes poor, and the drying efficiency is significantly reduced. From the perspective of not easily causing such problems, inorganic powder is advantageous.
[0148] The average particle size of the inorganic powder that does not interact is preferably 1 to 10,000 μm, more preferably 10 to 5,000 μm, and particularly preferably 100 to 1,000 μm. If the average particle size exceeds 10,000 μm, the effect of entering the gaps between cellulose fibers and inhibiting aggregation may not be achieved when removing the aqueous medium. On the other hand, if the average particle size is less than 1 μm, the hydrogen bonds between microfiber cellulose may not be inhibited due to the fineness.
[0149] In this specification, the average particle size of the inorganic powder that does not interact is the median particle size calculated from the volume-based particle size distribution measured by a particle size distribution measuring device (e.g., laser diffraction / scattering particle size distribution measuring device manufactured by Horiba, Ltd.) using the powder directly or in the form of a water dispersion.
[0150] As inorganic powder, examples include simple substances, oxides, hydroxides, carbonates, sulfates, silicates, sulfites, various clay minerals containing these compounds, and the like of metal elements in Groups I to VIII of the periodic table such as Fe, Na, K, Cu, Mg, Ca, Zn, Ba, Al, Ti, and silicon. Specifically, examples include barium sulfate, calcium sulfate, magnesium sulfate, sodium sulfate, calcium sulfite, zinc oxide, heavy calcium carbonate, light calcium carbonate, aluminum borate, aluminum oxide, iron oxide, calcium titanate, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, sodium hydroxide, magnesium carbonate, calcium silicate, clay, wollastonite, glass beads, glass powder, silica gel, dry silica, colloidal silica, silica sand, silica, quartz powder, diatomaceous earth, white carbon black, glass fiber, and the like. These inorganic fillers may contain multiple types. In addition, it may be an inorganic filler contained in waste paper pulp, or it may be a so-called regenerated filler obtained by regenerating inorganic substances in papermaking sludge.
[0151] Among them, it is preferred to use at least one inorganic powder selected from calcium carbonate, talc, white carbon, clay, calcined clay, titanium dioxide, aluminum hydroxide and recycled filler etc. which are suitable for use as fillers or pigments for papermaking, more preferably at least one selected from calcium carbonate, talc, clay, and particularly preferably at least any one of light calcium carbonate and heavy calcium carbonate. If calcium carbonate, talc, and clay are used, it is easy to be composited with matrices such as resins. In addition, since it is a general inorganic material, it has the advantage of rarely generating use restrictions. In addition, calcium carbonate is particularly preferred for the following reasons. When using light calcium carbonate, it is easy to constantly control the size and shape of the powder. Therefore, it has the following advantages: according to the size and shape of the cellulose fibers, the size and shape are adjusted in a manner that the effect of easily entering the gap and suppressing the coagulation of the cellulose fibers to each other is easily generated, so that the effect can be easily and accurately exerted. In addition, if heavy calcium carbonate is used, since heavy calcium carbonate is amorphous, it has the following advantages: even if there are fibers of various sizes in the slurry, it can enter the gaps during the fiber aggregation process when the aqueous medium is removed and suppress the aggregation of cellulose fibers.
[0152] The amount of inorganic powder that does not interact is preferably 1 to 9900 mass %, more preferably 5 to 1900 mass %, and particularly preferably 10 to 900 mass % relative to fibrous cellulose. If the amount is less than 1 mass %, the effect of entering the gaps between cellulose fibers and inhibiting aggregation may be insufficient. On the other hand, if the amount is greater than 9900 mass %, it may not be able to function as a cellulose fiber.
[0153] In addition, if the maleic anhydride modified resin and the inorganic powder that does not interact are used together, even if they are mixed under the conditions of their respective coagulation, the maleic anhydride modified resin and the inorganic powder that does not interact can also play the effect of preventing mutual coagulation. In addition, the surface area of the powder with a small particle size is large, and it is more susceptible to the influence of intermolecular forces than the influence of gravity, and as a result, it becomes easy to coagulate. Therefore, when the powder is mixed with the microfiber cellulose slurry, it is possible that the powder cannot be smoothly dispersed in the slurry or the powders coagulate with each other when the aqueous medium is removed, thereby failing to fully exert the effect of preventing the coagulation of microfiber cellulose. However, it is believed that if the maleic anhydride modified resin and the inorganic powder that does not interact are used together, the coagulation of itself can be alleviated.
[0154] When the maleic anhydride modified resin and the inorganic powder that does not interact are used together, the average particle size ratio of the maleic anhydride modified resin to the inorganic powder that does not interact is preferably 1:0.1 to 1:10000, more preferably 1:1 to 1:1000. It is believed that within this range, problems due to strong self-cohesion (for example, the powder cannot be smoothly dispersed in the slurry, or the powders aggregate with each other when the aqueous medium is removed) will not occur, and the effect of preventing the aggregation of microfibril cellulose can be fully exerted.
[0155] When the maleic anhydride modified resin and the inorganic powder that do not interact with each other are used together, the ratio of the mass % of the inorganic powder to the mass % of the maleic anhydride modified resin is preferably 1:0.01 to 1:100, and more preferably 1:0.1 to 1:10. It is believed that within this range, the different powders can prevent themselves from agglomerating. In other words, it is believed that within this range, problems caused by strong cohesion of the powder itself (for example, the powder cannot be smoothly dispersed in the slurry, or the powders agglomerate with each other when the aqueous medium is removed) will not occur, and the effect of preventing the aggregation of microfibril cellulose can be fully exerted.
[0156] (Dispersant)
[0157] The fibrous cellulose composite resin of this embodiment is preferably mixed with a dispersant. As the dispersant, an aromatic compound having an amine group and / or a hydroxyl group and an aliphatic compound having an amine group and / or a hydroxyl group are preferred.
[0158] Examples of aromatic compounds having an amino group and / or a hydroxyl group include anilines, toluidines, trimethylanilines, anisidines, tyramines, histamines, tryptamines, phenols, butylated hydroxytoluenes, bisphenol A, cresols, eugenols, gallic acids, guaiacols, picric acids, phenolphthalein, serotonins, dopamines, adrenaline, noradrenaline, thymols, tyrosines, salicylic acids, Class, methyl salicylate, anise alcohol, salicyl alcohol, mustard alcohol, diphenyl piperidine butanol, diphenyl carbinol, cinnamic alcohol, scopolamine, tryptophan, vanillyl alcohol, 3-phenyl-1-propanol, phenylethyl alcohol, phenoxyethanol, resveratrol, benzyl alcohol, benzoin, mandelic acid, mandelonitrile, benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, mellitic acid, cinnamic acid, etc.
[0159] Examples of aliphatic compounds having an amino group and / or a hydroxyl group include octanols, 2-ethylhexanols, nonanols, decanols, undecanols, lauryl alcohols, tridecanols, myristyl alcohols, pentadecyl alcohols, cetyl alcohols, stearyl alcohols, elaidic alcohols, oleyl alcohols, linoleyl alcohols, methylamines, dimethylamines, trimethylamines, ethylamines, diethylamines, ethylenediamines, triethanolamines, N,N-diisopropyl ethylamines, Amines, tetramethylethylenediamine, 1,6-hexanediamine, spermidine, spermine, adamantane, formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, octanoic acid, nonanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, heptadecanoic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, docosahexaenoic acid, sorbic acid, etc.
[0160] The above dispersants hinder the hydrogen bonding between cellulose fibers. Therefore, the microfiber cellulose is reliably dispersed in the resin during kneading. In addition, the above dispersants also have the effect of improving the compatibility of the microfiber cellulose and the resin. From this point of view, the dispersibility of the microfiber cellulose in the resin is improved.
[0161] The amount of the dispersant mixed is preferably 0.1 to 1000 parts by mass, more preferably 1 to 500 parts by mass, and particularly preferably 10 to 200 parts by mass relative to 100 parts by mass of the microfiber cellulose. If the amount of the dispersant mixed is less than 0.1 parts by mass, the improvement in the resin strength may be insufficient. On the other hand, if the amount of the dispersant mixed is more than 1000 parts by mass, it becomes excessive and there is a tendency for the resin strength to decrease.
[0162] In this regard, the maleic anhydride modified resin is used to improve compatibility and enhance the reinforcing effect by bonding the acid group with the carbamate group of the microfiber cellulose. Since the molecular weight is large, it is believed that it is also easily compatible with other resins, which helps to improve the strength. On the other hand, the dispersant is interposed between the hydroxyl groups of the microfiber cellulose to prevent aggregation, thereby improving the dispersibility in the resin, and since the molecular weight is smaller than that of the maleic anhydride modified resin, it can enter the narrow space between the microfiber cellulose that the maleic anhydride modified resin cannot enter, and play a role in improving dispersibility and thus improving strength. From the above aspects, it is appropriate that the molecular weight of the maleic anhydride modified resin is 2 to 2000 times, preferably 5 to 1000 times the molecular weight of the dispersant.
[0163] To explain this in more detail, inorganic powders that do not interact with each other hinder hydrogen bonds between microfiber celluloses by physically interposing them, thereby improving the dispersibility of microfiber cellulose. In contrast, maleic anhydride-modified resins improve compatibility by bonding the acid groups to the carbamate groups of microfiber cellulose, thereby improving the reinforcing effect. In this regard, it is the same as the dispersant in hindering hydrogen bonds between microfiber celluloses, but the inorganic powders that do not interact with each other are micron-sized, so they are physically interposed therebetween to inhibit hydrogen bonds. In addition, since the inorganic powders are rigid in themselves, they help to improve the physical properties of resins, etc. when compounded with resins, etc. On the other hand, the dispersant is at the molecular level and is extremely small, so it hinders hydrogen bonds in a way that covers the microfiber cellulose, and the effect of improving the dispersibility of the microfiber cellulose is high. However, if it remains in the resin, it may have the effect of reducing the physical properties.
[0164] (Method for producing composite resin)
[0165] The carbamate-modified microfiber cellulose and carbamate-modified pulp (or the aqueous dispersion of these fibrous celluloses) are mixed with maleic anhydride-modified resin and polyethylene as needed. The mixture (liquid) is preferably dried to form a dried product before kneading to form a composite resin. If dried in advance, it is not necessary to dry the fibrous cellulose during kneading, and the thermal efficiency is good.
[0166] The mixture can be dried by selecting one or more of rotary kiln drying, disc drying, airflow drying, medium flow drying, spray drying, drum drying, screw conveyor drying, paddle drying, single-screw kneading drying, multi-screw kneading drying, vacuum drying, stirring drying, etc.
[0167] The mixture is preferably dehydrated before drying to obtain a dehydrated product. The dehydration can be carried out by selecting one or more dehydrating devices such as a belt press, a screw press, a filter press, a double roll machine, a double mesh former, a valveless filter, a center disc filter, a membrane treatment, a centrifuge, etc.
[0168] The dried mixture (dried product) is preferably pulverized in advance to form a powder. The pulverization of the dried product can be carried out by using one or more selected from a bead mill, a kneader, a disperser, a twist mill, a cutting mill, a hammer mill, and the like.
[0169] The average particle size of the powder is preferably 1 to 10,000 μm, more preferably 10 to 5,000 μm, and particularly preferably 100 to 1,000 μm. If the average particle size of the powder exceeds 10,000 μm, the kneading property may be deteriorated. On the other hand, in order to make the average particle size of the powder less than 1 μm, a large amount of energy is required, which is not economical.
[0170] The average particle size of the powder can be controlled by controlling the degree of pulverization or by classification using a classifying device such as a filter or a cyclone separator.
[0171] The bulk specific gravity of the mixture (powder) is preferably 0.03 to 1.0, more preferably 0.04 to 0.9, and particularly preferably 0.05 to 0.8. A bulk specific gravity exceeding 1.0 means that the hydrogen bonds between the fibrous cellulose are stronger and it is not easy to disperse in the resin. On the other hand, a bulk specific gravity below 0.03 is disadvantageous in terms of transportation cost.
[0172] The bulk specific gravity is a value measured in accordance with JIS K7365.
[0173] The water content of the mixture (powder) is preferably 50% or less, more preferably 30% or less, and particularly preferably 10% or less. If the water content is higher than 50%, the energy required for kneading with the resin is enormous, which is uneconomical.
[0174] The moisture content is a value calculated by the following formula by keeping the sample at 105° C. for 6 hours or more in a constant temperature dryer and defining the mass at the point when the mass change is no longer observed as the mass after drying.
[0175] Fiber moisture content (%) = [(mass before drying - mass after drying) ÷ mass before drying] × 100
[0176] The dried pulverized product is kneaded to produce a fibrous cellulose composite resin. The composite resin using maleic anhydride-modified polypropylene and polyethylene has excellent processing suitability and can be drawn into strands even when the blending ratio of the fibrous cellulose is as high as 50% by mass or more.
[0177] The blending ratio of the fibrous cellulose to the total amount of the composite resin is, for example, 50% by mass or more, preferably 50 to 70% by mass, and more preferably 55 to 68% by mass. If the blending ratio exceeds 70% by mass, the processing suitability of the composite resin may be insufficient even in the present embodiment.
[0178] The kneading of the dry powder can be performed, for example, by the same method as in the case where a resin is further added and kneaded as described below. Therefore, the description is omitted here.
[0179] The fibrous cellulose composite resin of the present embodiment can be kneaded with other resins and diluted to a mixing ratio of fibrous cellulose of, for example, 10%. The kneading can be performed by, for example, a method of mixing the composite resin of the present embodiment as a powder with other resins in a granular form, or a method of first melting other resins and then adding the composite resin of the present embodiment as a powder to the melt.
[0180] The kneading treatment can be carried out by selecting one or more than two kinds of kneading machines from a single screw or a twin screw or more multi-screw kneading machine, a mixing roll, a kneader, a roll mill, a Banbury mixer, a screw press, a disperser, etc. Among these devices, a twin screw or more multi-screw kneading machine is preferably used. It is also possible to use two or more twin screw or more multi-screw kneading machines in parallel or in series.
[0181] The temperature of the kneading treatment is not less than the glass transition temperature of the resin, and varies depending on the type of the resin, but is preferably 80 to 280°C, more preferably 90 to 260°C, and particularly preferably 100 to 240°C.
[0182] As the other resin, at least any one of a thermoplastic resin and a thermosetting resin can be used.
[0183] As the thermoplastic resin, for example, one or more kinds can be selected from polyolefins such as polypropylene (PP) and polyethylene (PE), polyester resins such as aliphatic polyester resins and aromatic polyester resins, polystyrene, polyacrylic resins such as methacrylate and acrylate, polyamide resins, polycarbonate resins, polyacetal resins, etc.
[0184] Among them, at least one of polyolefin and polyester resin is preferably used. In addition, as polyolefin, polypropylene is preferably used. In addition, as polyester resin, as aliphatic polyester resin, for example, polylactic acid, polycaprolactone, etc. can be exemplified, as aromatic polyester resin, for example, polyethylene terephthalate, etc. can be exemplified, but it is preferable to use a biodegradable polyester resin (also referred to as "biodegradable resin").
[0185] As the biodegradable resin, one or more kinds selected from, for example, hydroxycarboxylic acid-based aliphatic polyesters, caprolactone-based aliphatic polyesters, dibasic acid polyesters, and the like can be used.
[0186] As the hydroxycarboxylic acid-based aliphatic polyester, one or more kinds can be selected from homopolymers of hydroxycarboxylic acids such as lactic acid, malic acid, gluconic acid, and 3-hydroxybutyric acid, copolymers using at least one of these hydroxycarboxylic acids, etc. Among them, polylactic acid, copolymers of lactic acid and the above hydroxycarboxylic acids other than lactic acid, polycaprolactone, and copolymers of at least one of the above hydroxycarboxylic acids and caprolactone are preferably used, and polylactic acid is particularly preferably used.
[0187] As the lactic acid, for example, L-lactic acid, D-lactic acid, etc. can be used. These lactic acids may be used alone or in combination of two or more.
[0188] As the caprolactone-based aliphatic polyester, one or more kinds can be selected from, for example, homopolymers of polycaprolactone, copolymers of polycaprolactone and the above-mentioned hydroxycarboxylic acids, and the like.
[0189] As the dibasic acid polyester, one or more kinds selected from, for example, polybutylene succinate, polyethylene succinate, polybutylene adipate, and the like can be used.
[0190] The biodegradable resin may be used alone or in combination of two or more.
[0191] As the thermosetting resin, for example, phenolic resin, urea resin, melamine resin, furan resin, unsaturated polyester, diallyl phthalate resin, vinyl ester resin, epoxy resin, urethane resin, silicone resin, thermosetting polyimide resin, etc. can be used. These resins can be used alone or in combination of two or more.
[0192] Regarding the mixing ratio of the total amount of fibrous cellulose and resin, it is preferred that the fibrous cellulose is 1 mass part or more and the resin is 99 mass parts or less, more preferably the fibrous cellulose is 2 mass parts or more and the resin is 98 mass parts or less, and particularly preferably the fibrous cellulose is 3 mass parts or more and the resin is 97 mass parts or less. In addition, it is preferred that the fibrous cellulose is 50 mass parts or less and the resin is 50 mass parts or more, more preferably the fibrous cellulose is 40 mass parts or less and the resin is 60 mass parts or more, and particularly preferably the fibrous cellulose is 30 mass parts or less and the resin is 70 mass parts or more. In particular, if the fibrous cellulose is 10 to 50 mass parts, the strength of the resin composition, especially the strength of the bending strength and the tensile modulus, can be significantly improved.
[0193] In addition, the content ratio of the fibrous cellulose and the resin contained in the finally obtained resin composition is usually the same as the above-mentioned mixing ratio of the fibrous cellulose and the resin.
[0194] (other)
[0195] The fibrous cellulose composite resin or the composite resin obtained by diluting the composite resin can be kneaded again as needed and then molded into a desired shape. The size, thickness, shape, etc. of the molded product are not particularly limited, and can be, for example, sheet, granular, powder, fibrous, etc.
[0196] The temperature during the molding process is equal to or higher than the glass transition temperature of the resin, and varies depending on the type of the resin, but is, for example, 90 to 260°C, and preferably 100 to 240°C.
[0197] The kneaded product can be formed by, for example, mold molding, injection molding, extrusion molding, hollow molding, foaming molding, etc. In addition, the kneaded product can be spun into fibers and mixed with the above-mentioned plant materials to form a mat shape or a plate shape. The mixed fibers can be, for example, simultaneously deposited by air lay.
[0198] As the apparatus for molding the kneaded product, one or more kinds of apparatuses selected from, for example, an injection molding machine, an injection molding machine, a hollow molding machine, a blow molding machine, a compression molding machine, an extrusion molding machine, a vacuum molding machine, an air pressure molding machine, etc. can be used.
[0199] The above molding can be carried out after kneading, or the kneaded material can be temporarily cooled, fragmented using a crusher, etc., and then the fragments are put into a molding machine such as an extruder or injection molding machine. Of course, molding is not a necessary condition of the present invention.
[0200] Example
[0201] Next, examples of the present invention will be described.
[0202] (Test Example 1)
[0203] A urea aqueous solution having a solid content concentration of 30% was mixed with conifer bleached kraft pulp having a moisture content of 50% or less at a ratio of pulp to urea of 100:50 in terms of mass ratio based on solid content, and then dried at 105° C. Thereafter, the mixture was allowed to stand at 160° C. for 1 hour to react, thereby obtaining a carbamate-modified pulp (CA pulp).
[0204] The obtained urethane-modified pulp was diluted with distilled water and stirred, and dehydration and washing were repeated twice to adjust the solid content concentration to 3.0% by mass, thereby obtaining washed urethane-modified pulp.
[0205] The washed urethane-modified pulp was beaten with a beater until the fineness (the ratio of fibers of 0.2 mm or less in the fiber length distribution measurement by FS5) was 40% or more to obtain urethane-modified microfiber cellulose (CAMFC).
[0206] 20.7 g of maleic anhydride-modified polypropylene and 6.8 g of polyethylene powder were added to 916 g of urethane-modified microfiber cellulose having a solid content concentration of 3.0% by mass, and after stirring, the mixture was heated and dried using a contact dryer heated to 140° C. to obtain a fibrous cellulose-containing material having a moisture content of 5 to 22%.
[0207] The fibrous cellulose-containing material was kneaded with a twin-screw kneader at 170° C. and 75 rpm, and cut into a cylindrical shape with a diameter of 2 mm and a length of 2 mm, thereby obtaining a fibrous cellulose composite resin having a fiber blending ratio of 66.7%.
[0208] A fibrous cellulose composite resin having a fiber blending ratio of 66.7% and PP pellets were dry-blended in a dry mass ratio of 9:51, kneaded with a twin-screw mixer at 170°C and 75 rpm, and cut into a cylindrical shape of 2 mm in diameter and 2 mm in length with a pelletizer to obtain a fibrous cellulose composite resin having a fiber blending ratio of 10%. The fibrous cellulose composite resin having a fiber blending ratio of 10% was injection molded at 180°C into a rectangular test piece (length 59 mm, width 9.6 mm, thickness 3.8 mm).
[0209] (Other test examples)
[0210] For the fibrous cellulose, other tests were conducted by replacing part or all of the carbamate-treated microfibril cellulose with carbamate-treated pulp, changing the fineness (Fine rate) of the fibrous cellulose, etc. The details are shown in Table 1.
[0211] For each test piece obtained, the inclusion area ratio (mm 2 / m 2), dispersibility (the case where less than 2 visually confirmed agglomerates are marked as ○, the case where 2 or more visually confirmed agglomerates are marked as △, and the case where 2 or more agglomerates with a major diameter of 1 mm or more are marked as ×), flexural modulus (relative value when the flexural modulus of the base PP is set to 100), flexural strength (relative value when the flexural strength of the base PP is set to 100), and MFR (200°C 10kgf) are shown in Table 1. It should be noted that the inclusion area ratio is measured in accordance with JIS P 8145:2011. In addition, in the bending test, the investigation was conducted in accordance with JIS K7171:2008. It should be noted that the adjusted fineness (Fine) rate refers to the fineness (Fine) rate of the fiber obtained by mixing the urethanized microfiber cellulose and the urethanized pulp.
[0212] [Table 1]
[0213]
[0214] (Inspection)
[0215] It is known that the dispersibility of carbamate-modified microfiber cellulose is improved by mixing it with carbamate-modified pulp. It is also known that the degree of improvement varies depending on the fineness of the carbamate-modified microfiber cellulose. It is also known that the bending properties are insufficient when only pulp is used, and carbamate-modified microfiber cellulose is required. It is believed that this is because the microfiber cellulose is fibrillated by beating, the contact points with the resin increase, and the bending properties are improved when added to the composite resin.
[0216] Industrial Applicability
[0217] The present invention can be used as a fibrous cellulose composite resin.
Claims
1. A fibrous cellulose composite resin, characterized in that Contains fibrous cellulose and resin, The fibrous cellulose includes carbamate-treated microfiber cellulose having an average fiber length of 0.15 mm to 0.90 mm and in which a part or all of the hydroxyl groups are substituted with carbamate groups, and carbamate-treated pulp having an average fiber length of 1.0 mm to 5.0 mm and in which a part or all of the hydroxyl groups are substituted with carbamate groups. The fineness ratio of the urethanized microfiber cellulose is 70% or less.
2. The fibrous cellulose composite resin according to claim 1, wherein The ratio of the amount of introduced carbamate groups of the carbamate-treated microfiber cellulose to that of the carbamate-treated pulp is 0.3 to 4.
0.
3. The fibrous cellulose composite resin according to claim 1, wherein The ratio of the average fiber diameters of the urethanized microfiber cellulose and the urethanized pulp is 1.1 to 50.
0.
4. The fibrous cellulose composite resin according to claim 1, wherein The ratio of the average fiber length of the urethanized microfiber cellulose to the average fiber length of the urethanized pulp is 1.1 to 20.
0.
5. The fibrous cellulose composite resin according to claim 1, wherein The dry mass ratio of the urethanized microfiber cellulose to the urethanized pulp is 0.01-100.
6. The fibrous cellulose composite resin according to claim 1, wherein comprising a maleic anhydride modified resin as the resin, The blending ratio of the fibrous cellulose is 50% by mass or more.
Citation Information
Patent Citations
Fibrous cellulose composite resin, manufacturing method thereof, and resin reinforcing material
JP2020163651A